Correction to: Frequency of fatigue and its changes in the first 6 months after traumatic brain injury: results from the CENTER-TBI study (Journal of Neurology, (2021), 268, 1, (61-73), 10.1007/s00415-020-10022-2) - Andelic, Nada; Roe, Cecilie; Bullet, Cathrine Brunborg; Bullet, Marina Zeldovich; Lovstad, Marianne; Loke, Daniel; Borgen, Ida M.; Bullet, Daphne C. Voormolen; Howe, Emilie I.; Bullet, Marit V. Forslund; Dahl, Hilde M.; Von Steinbuechel, Nicole; et al. (Journal of Neurology, 2021)
The original version of this article unfortunately contained a mistake.
CRIS-Team Scopus Importer:2023-03-08